My Holistic Data Share: A WEB3 Data Share Application: Extending Beyond Finance to Privacy-Protected Decentralized Share of Multi-Dimensional Data to Enhance Global Healthcare - SATHYA KRISHNASAMY (Blockchain in Healthcare Today)
Abstract